2006
DOI: 10.1002/zaac.200500470
|View full text |Cite
|
Sign up to set email alerts
|

Di‐Benzo‐18‐Crown‐6 and its Derivatives as Ligands in the Search for Ion Channels

Abstract: Abstract. Based on the previously reported one-dimensional chan-, which is realized by stacking of crown ether molecules (DB18C6 ϭ dibenzo-18-crown-6), other synthetic approaches towards ionic channels and their results are presented in this paper. The "cutting out" approach using DB18C6 as scissor, applied on NaI, yields the compound [Naʚ(DB18C6)I(THF)]-[Naʚ(DB18C6)(H 2 O) 2 ]I(THF) 2 (CHI 3 ) (1), in high yield. It is based on a neutral and a cationic complex of sodium by DB18C6 linked via H-bonding to give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
2
12
1
2
Order By: Relevance
“…The shortest distance is the bond contact of the interconnected bromine molecule with 230.8 and 235.4 pm in [BzPh 3 P] 2 [Br 8 ] and [Q] 2 [Br 8 ], respectively. Fromm et al also reported on a crown ether salt [H 3 O(Br 4 ‐dibenzo‐18‐crown‐6)][Br 3 · Br 2 ] 54. This description is not in accordance with the reported crystal structure and therefore better described as [H 3 O(Br 4 ‐dibenzo‐18‐crown‐6)] 2 [Br 8 ] 55…”
Section: Polybromidesmentioning
confidence: 92%
“…The shortest distance is the bond contact of the interconnected bromine molecule with 230.8 and 235.4 pm in [BzPh 3 P] 2 [Br 8 ] and [Q] 2 [Br 8 ], respectively. Fromm et al also reported on a crown ether salt [H 3 O(Br 4 ‐dibenzo‐18‐crown‐6)][Br 3 · Br 2 ] 54. This description is not in accordance with the reported crystal structure and therefore better described as [H 3 O(Br 4 ‐dibenzo‐18‐crown‐6)] 2 [Br 8 ] 55…”
Section: Polybromidesmentioning
confidence: 92%
“…Later, Fromm et al. also reported the salt [H 3 O(Br4‐dibenzo‐18‐crown‐6][Br 3 ⋅Br 2 ] . Although the stoichiometry is correct, the polybromine dianion present in the crystal structure is clearly [Br 8 ] 2− .…”
Section: Polybromine Anionsmentioning
confidence: 99%
“…This distance is hence somewhat shorter than a standard intermolecular distance of 2.8 Å between oxygen atoms of two neighbouring water molecules (r(O) ¼ 1.4 Å ). However, a number of structures have been reported to show O-O distances between neighbouring water molecules in the range of 2.0-2.4 Å [11][12][13].…”
Section: Resultsmentioning
confidence: 97%